Meningkatkan Hasil Belajar Siswa Pada Materi Pembelajaran Matematika Tentang Perbandingan Menggunakan Pendekatan Pemecahan Masalah Di Kelas VII SMPN 21 Kota Tasikmalaya Tahun Pelajaran 2022/2023 - Evi Farida (Universitas Majalengka, 2023)
The purpose of this research is as an effort to improve student learning outcomes regarding the volume of cubes, blocks and pyramids using a problem solving approach, presenting more effective learning that can help students improve their achievements. This research was a Classroom Action Research with 33 class VII students at SMPN 21 Kota Tasikmalaya as subjects, consisting of 23 male students and 10 female students. Each cycle consisted of four activities, namely: planning, implementing, observing, and reflection. Kemmis-Taggart Classroom Action Research Model. The data collection used is the test technique and observation technique. While processing the data through quantitative and qualitative data. The results of this study showed an increase, this was evident from the results of observing the learning process in the form of research observation sheets, which consisted of observations on the teacher's ability to design lesson plans, there was an increase of 25.00%, namely in cycle I it was worth 57.14% and in cycle II worth 81.14%. In the process of implementing learning there is also an increase of 31.82%, namely in the first cycle it is worth 58.33%, in the second cycle it is worth 90.15%, while student activities also have an increase of 32.69%, namely in the first cycle it is worth 55.77 %, in cycle II is worth 88.46%. And the ability of student learning outcomes has increased by 24.87%, it is proven that the acquisition value of the evaluation cycle I is worth 63.85% while in cycle II it is worth 88.72%. Therefore, the teacher should use a problem-solving approach that can help students overcome learning difficulties, starting from conditioning the readiness of students related to the material, explaining the subject matter continuously and carrying out evaluations and the results obtained from this research.